2008
DOI: 10.4103/0970-0218.40878
|View full text |Cite
|
Sign up to set email alerts
|

A study of occurrence of domestic accidents in semi-urban community

Abstract: Context:Domestic accidents are worldwide public health problems. The consequences of a domestic accident may prove disastrous as it may result in disability and loss of productivity. In this context, the present study was carried out to characterize the occurrence of domestic accidents in a semi-urban community.Aims:To study the incidence of domestic accident in a semi-urban community and its association with various epidemiological factors.Settings and Design:Community-based cross-sectional study of 796 house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
56
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 2 publications
15
56
1
4
Order By: Relevance
“…7,10,[14][15][16] Falls was more commonly reported among children and elderly, which is consistent with the results of Sudhir et al and Bhanderi et al 8,10 However, studies conducted in Avsarogullari et al, Neghab et al and by Chaurasia et al, it was observed that higher proportion of burns as most common domestic accident. 11,13,17 Shawon et al reported that courtyards and kitchen were the common places where domestic accidents happened, where as in our study, they were common in front yard and kitchen.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…7,10,[14][15][16] Falls was more commonly reported among children and elderly, which is consistent with the results of Sudhir et al and Bhanderi et al 8,10 However, studies conducted in Avsarogullari et al, Neghab et al and by Chaurasia et al, it was observed that higher proportion of burns as most common domestic accident. 11,13,17 Shawon et al reported that courtyards and kitchen were the common places where domestic accidents happened, where as in our study, they were common in front yard and kitchen.…”
Section: Discussionsupporting
confidence: 80%
“…Similar to our study, Bhanderi et al conducted a study in a semi urban area of Gujarat where in the prevalence was very less (1.7%) because of better housing conditions and the safety precautions taken to avoid any such injuries. 10 Falls was the most common domestic accidents reported in our study that is similar to that of studies done by Masthi et al, Sudhir et al, Shawon et al and also in the study done by Bhanderi et al [7][8][9][10] However, there are some studies conducted in Turkey, Pakistan and Iran that reported burns as the most common domestic accident. [11][12][13] This variation could be due to the differences in the lifestyle, habits and level of people"s awareness among these countries.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…16 Another study done in Gujarat by Dinesh et al showed a very low prevalence of fall (3.4%) among elders above 60 years of age but again the definition of fall used to capture it as a fall was not made known. 17 It has been difficult to compare the magnitude of burden of fall between the various studies due to lack of uniformity in the operational definition of fall. Hence, it is difficult to conclude whether the varying burden of falls widely among different countries is due to lack of uniformity in the operational definition or a real one.…”
Section: Discussionmentioning
confidence: 99%
“…However, falling was the most frequent cause of domestic accidents among urban families. Many studies have been conducted to find factors related to falling in communities (17,18). These results show that migrated families who were less familiar with new equipment in their new houses were not able to use them correctly.…”
Section: Discussionmentioning
confidence: 99%